Manufacturing system engineering: Horizontal directional drilling (drilling and tooling) - Chew, Lim Sim; Subramanie, Kalaiyani A/P; Supramaniam, Kanagambikai A/P; Sugumuhran, Saambavi A/P; Rajemi, Mohamad Farizal (2013)
Horizontal directional drilling (HDD), also known as directional drilling as one of the methods of installing underground pipe and conduit.In this research this drilling method is being discussed meticulously.This research reveals the operation and control system of the HDD.Besides that, also discussed are the advantages and disadvantages of using this technology.This research will give better understanding of the HDD to the engrossed parties.